2014
DOI: 10.5761/atcs.oa.13.02252
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Human Atrial Natriuretic Peptide Infusion in Non-Dialysis Patients with Chronic Kidney Disease Undergoing Isolated Coronary Artery Bypass Grafting: the NU-HIT Trial for CKD-II

Abstract: Background: Chronic kidney disease (CKD) is an important risk factor for cardiac surgery. In the most recently reported NU-HIT trial for CKD with CKD patients underwent coronary artery bypass grafting (CABG) as subjects, carperitide was reported to be effective in terms of renal function. In the present study, a subanalysis was performed on patients registered in the NU-HIT trial for CKD from the standpoint of renin-angiotensin system, natriuresis and renal function. Methods: 303 patients with CKD who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…We have previously performed several prospective trials to investigate the effects of carperitide in non-dialysis patients undergoing cardiac surgery, and we have reported that this drug has a cardioprotective effect, a renoprotective effect, counteracts the adverse influence of cardiopulmonary bypass, inhibits the renin-angiotensin-aldosterone system (RAAS), inhibits left ventricular remodeling, and has an antiarrhythmic effect. [13][14][15][16][17][18][19] With regard to the renoprotective effect of carperitide, we have found both acute and longterm avoidance of dialysis, RAAS inhibition, and a potent natriuretic action in non-dialysis patients with CKD. 16,17) Accordingly, we performed the present retrospective investigation to assess the effectiveness of carperitide in dialysis patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously performed several prospective trials to investigate the effects of carperitide in non-dialysis patients undergoing cardiac surgery, and we have reported that this drug has a cardioprotective effect, a renoprotective effect, counteracts the adverse influence of cardiopulmonary bypass, inhibits the renin-angiotensin-aldosterone system (RAAS), inhibits left ventricular remodeling, and has an antiarrhythmic effect. [13][14][15][16][17][18][19] With regard to the renoprotective effect of carperitide, we have found both acute and longterm avoidance of dialysis, RAAS inhibition, and a potent natriuretic action in non-dialysis patients with CKD. 16,17) Accordingly, we performed the present retrospective investigation to assess the effectiveness of carperitide in dialysis patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] With regard to the renoprotective effect of carperitide, we have found both acute and longterm avoidance of dialysis, RAAS inhibition, and a potent natriuretic action in non-dialysis patients with CKD. 16,17) Accordingly, we performed the present retrospective investigation to assess the effectiveness of carperitide in dialysis patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to preoperative severe CKD and cardiac dysfunction, prolonged aortic clamping and non-use of carperitide had an effect on long-term MACCE. Our clinical research on perioperative low-dose infusion of carperitide has demonstrated that this drug compensates for the deficiencies of cardiopulmonary bypass and also provides organ protection, 10,11) with both effects being stronger in high risk patients. 12) Accordingly, administration of carperitide to elderly patients undergoing cardiac surgery could be effective for decreasing postoperative complications and protecting vital organs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Carperitide is known to exert cardio and renoprotective effects even in patients with mild to moderate renal dysfunction. 26) It is intriguing to examine whether perioperative Carperitide improves postoperative outcomes in mitral valve surgery.…”
Section: Discussionmentioning
confidence: 99%